Strategi Komunikasi Pemasaran di Media Sosial Youtube dalam Membangun Professional Brand Image - Alaika Amaly Khaira; Arfian Suryasuciramdhan; Dhiyandra Prasetya Gusti; Fauzan Azima; Rahma Aniq Aulia (Badan Penerbit STIEPARI Press, 2025)
The development of information and communication technology has brought significant transformation in marketing strategies, especially in building brand image professionally. One of the local products that utilize YouTube social media intensively is Sirup Marjan, which is widely known in Indonesia as a beverage product that is synonymous with the moment of Ramadan. This study aims to identify and analyze the role of Youtube social media in shaping Sirup Marjan's professional image through content strategy, utilization of social media platforms, and emotional approaches in its digital campaigns. This research uses a descriptive qualitative method with a literature study approach and observation of Marjan's digital activities on the YouTube platform. The results show that digital media is not only a promotional tool, but also a key tool in building emotional closeness with audiences, strengthening brand storytelling, and increasing consumer loyalty. Through consistent visualization, evocative narratives, and collaboration with influencers and content creators, Sirup Marjan has succeeded in shaping professional, relevant, and aspirational brand perceptions in the minds of consumers. In addition, the annual Ramadhan-themed campaign became a strategic momentum to strengthen the brand identity that is religious, and has a value of togetherness. The conclusion of this research shows that digital media plays an important role in the process of forming a strong and sustainable branding image, especially for products that want to maintain their existence and competitiveness in the digital era.